Rolling thunder revue a Bob Dylan story by Martin Scorsese - Myers, David 1914-2004; Alk, Howard 1930-1982; Goldsmith, Paul ca. 20. Jh; Levine, Michael; Kuras, Ellen 1959-; Dylan, Bob 1941-; Dylan, Bob 1941-; Ginsberg, Allen 1926-1997; Smith, Patti 1946- (<<The>> Criterion collection, 2021)
"In 1975, in an America defined by both the self-mythologizing pomp of the upcoming bicentennial and ongoing sociopolitical turmoil, Bob Dylan and a band of troubadours—including luminaries such as Joan Baez, Allen Ginsberg, and Joni Mitchell - embarked on a now-legendary tour known as the Rolling Thunder Revue, a freewheeling variety show that was part traveling counterculture carnival, part spiritual pilgrimage. Director Martin Scorsese blends behind-the-scenes archival footage, interviews, and narrative mischief, with a magician’s sleight of hand, into a zeitgeist-defining cultural record that is as much a concert "documentary" as it is a slippery, chimerical investigation into memory, time, truth, and illusion. At the center of it all is the magnetic Dylan, a sphinxlike philosopher-poet singing, with electrifying conviction, to the soul of an anxious nation."[criterion.com]
Original: USA 2019
director-approved special edition features: new 4K digital master, approved by director Martin Scorsese ; new interviews with Scorsese, editor David Tedeschi, and writer Larry "Ratso" Sloman ; restored footage of never-before-seen "Rolling thunder revue" performances of "Tonight i’ll be staying here with you" and "Romance in Durango," and of a new, extended cut of "Tangled up in blue" ; restoration demonstration ; trailer ; English subtitles for the deaf and hard of hearing ; English descriptive audio ; plus: a new essay by novelist Dana Spiotta
Bildformat 1.33:1, 1.78:1
Keywords: Film; DVD-Video